2000
DOI: 10.1002/1097-4628(20001031)78:5<1134::aid-app230>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

The flame‐retardant polyester fiber: Improvement of hydrolysis resistance

Abstract: As far as the flame-retardant polyester fibers are concerned, the copolymerization of phosphorus retardants is the most common method. But a serious problem is that the phosphorus-containing polymer is easily hydrolyzed. We investigated the flame retardancy and the hydrolysis properties of two poly(ethylene terephthalate) (PET) fibers, one with a phosphorus compound as a side chain (side-chain type: HEIM Toyobo Co., Ltd.), and one with a phosphorus compound inserted in the polymer backbone (main-chain type). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 4 publications
0
25
0
Order By: Relevance
“…Thermal degradation in a nitrogen flow showed similar trends for the two types of FRs: the FR polyesters degraded at lower temperatures than the normal polyesters. Sato et al9 proposed that a phosphorous‐containing polymer changes into a metaphosphoric acid and then into a polyphosphoric acid, and they assumed that the degradation of a pendant‐type polyester would be slower than that of a main‐chain type, but both polymers have the same flame retardancy. However, in this research, we observed a difference in the thermal degradation under heating and at a constant high temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal degradation in a nitrogen flow showed similar trends for the two types of FRs: the FR polyesters degraded at lower temperatures than the normal polyesters. Sato et al9 proposed that a phosphorous‐containing polymer changes into a metaphosphoric acid and then into a polyphosphoric acid, and they assumed that the degradation of a pendant‐type polyester would be slower than that of a main‐chain type, but both polymers have the same flame retardancy. However, in this research, we observed a difference in the thermal degradation under heating and at a constant high temperature.…”
Section: Resultsmentioning
confidence: 99%
“…They did not examine the diethylene glycol (DEG) content in the polyesters and did not consider the thermal degradation caused by DEG. Sato et al9 compared the acidic hydrolytic resistance of the fibers according to the monomer types. They concluded that the flame retardancy was controlled by the phosphorous content and acidic hydrolytic resistance of the polymers and that a pendant type was better than a main‐chain type.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating a chemically reactive phosphorus‐containing monomer into the polymer chain is one of the most efficient methods of improving the flame retardancy of polyesters. There have been many reports on the copolymerization of flame‐retardant monomers into polyester chains 10–24. Chang et al 11, 12 studied the thermal degradation of phosphorus‐containing copolyesters and investigated the synthesis of side‐chain‐type copolyesters containing the phosphorus linking pendent groups by charging 9,10‐dihydro‐10‐[2,3‐di(hydroxycarbonyl)propyl]‐10‐phosphaphenanthrene‐10‐oxide, terephthalic acid and ethylene glycol in one reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Asrar et al 13 studied the synthesis of main‐chain‐type copolyesters of ethylene terephthalate and 2‐carboxyethyl(phenylphosphinic) acid and found that 2‐carboxyethyl(phenylphosphinic) acid can be copolymerized with terephthalic acid and ethylene glycol in the conventional melt polymerization process used for PET. The flame retardancy and the hydrolytic stability of two polyester fibers fabricated from the aforementioned copolyesters have been investigated by Sato et al 14 Both types of fibers had almost the same flame retardancy, but the main‐chain type was hydrolyzed about twice as fast as the side‐chain type, which led to a decrease of toughness immediately. Wang et al have synthesized some novel phosphorus‐containing copolyesters 15–18.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Such an approach is readily adaptable to step-polymerization polymers such as polyesters and thermoset plastics such as epoxy resins. [6][7][8][9][10][11][12][13] Remarkably, the flammability of polystyrenes with flame-retardant units covalently bonded to the polymer chain has been recently reported. 3,5,[14][15][16] The char residue of phosphoruscontaining copolymers after combustion was substantial because of the condensed-phase flameretardant action of phosphorus.…”
Section: Introductionmentioning
confidence: 99%